Characteristics of Brick Workers and C- Reactive Protein (CRP) Levels Using the Agglutination Method - NAZWA MUTIA AZAHRA; Defi Nurul Hayati; Zahrani Amelia Isza; Aisha Najwa Ainy; Alya Putri Rahayu; Inez Naura Sabrina; Dini Rismawati; Dwi Randi Musoleh (Tadulako University, 2026)
Chronic exposure to dust in the brick industry work environment has the potential to increase the risk of systemic inflammation and respiratory disorders, which can be identified through C-Reactive Protein (CRP) levels as an inflammation biomarker. This study aims to describe CRP levels in brick industry workers as an early detection step for inflammatory processes and a basis for preventing work-related health risks. In this descriptive study, 40 brick workers in Banyumas Regency were selected based on inclusion and exclusion criteria, with examinations conducted at the Medical Laboratory Technology Laboratory of UMP. CRP levels were measured using the latex agglutination method on blood samples, and data analysis considered respondent characteristics such as use of personal protective equipment (PPE), smoking habits, age, and duration of work. The results showed that most workers did not use PPE (38 people) and had smoking habits (33 people), but the majority showed negative CRP results (39 people), with only 1 worker experiencing elevated CRP at titer 1:2 with a level of 12 IU/mL. This study concludes that most brick industry workers have not experienced acute systemic inflammation, while factors such as age and lifestyle are suspected to play a role in elevated CRP levels in certain individuals.